The European Union's Screening Framework for Foreign Direct Investment: Consequences for External Relations - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2020)
The Lisbon Treaty gives the European Union (EU) institutions new external compe-tences, including foreign direct investment (FDI) inthe common trade policy. Using these competences the European Commission formulated aproposal for aregulation establishing the screening framework for FDI, which entered into force inApril 2019. The aim ofthis paper isto discuss the issue ofFDI screening asan element ofpoli-cies towards FDI applied bydeveloped countries, toassess the justifications for its introduction, aswell asthe potential consequences ofthe screening framework for inflowing FDI into the EU. Aneed toprotect the EU's strategic economic interests inrelations with third countries was the reason for the introduction ofthe new tool atthe EU level. The new system ofscreening FDI inflows into the EU isnot central-ized. The right toscreen remains the sole responsibility ofthe Member States. The co-ordination mechanism atthe level ofthe EU which has been constructed seems togive guarantees that common interests will beprotected. The economic and politi-cal consequences ofthe EU's screening framework for FDI should beforeseen. Apart from administrative and compliance costs, aswell asuncertainty and delays related toinvestment decision processes, two categories ofpotential consequences seem tobe important. These are the expected reduced access tocapital bysome Member States, especially the 'new' ones, and the worsening ofrelations with external part-ners, especially China.
Keywords: F21; F23; F42; K33; 330; Foreign direct investment (FDI); screening framework; the European Union; external relations; Chinese investment abroad